66.0k views
4 votes
How do you do this question?

How do you do this question?-example-1
User GordonM
by
5.6k points

1 Answer

3 votes

Answer:

6/5

Divergent

Explanation:

aₙ = (-6)ⁿ / (n 5ⁿ⁺²)

aₙ₊₁ = (-6)ⁿ⁺¹ / ((n+1) 5ⁿ⁺³)

lim(n→∞)│aₙ₊₁ / aₙ│

lim(n→∞)│[(-6)ⁿ⁺¹ / ((n+1) 5ⁿ⁺³)] / [(-6)ⁿ / (n 5ⁿ⁺²)]│

lim(n→∞)│[(-6)ⁿ⁺¹ / ((n+1) 5ⁿ⁺³)] × [(n 5ⁿ⁺²) / (-6)ⁿ]│

lim(n→∞)│[(-6)ⁿ⁺¹ / (-6)ⁿ] × [(n 5ⁿ⁺²) / ((n+1) 5ⁿ⁺³)]│

lim(n→∞)│-6 × n / (5 (n+1))│

lim(n→∞) (6n / (5n + 5))

6/5

The limit is greater than 1, so the series diverges.

User Smoreno
by
5.9k points